"Determination of relationships between two species of bats Rousettus aegyptiacus & Myotis myotis according to the immune response of Rabies" - ابراهيم نهلة (Latakia University Journal -Biological Sciences Series, 2021)
Research we performed to compare the immune response between two species of bats Roussetus aegyptiacus and Myotis myotis according to the immune response against RABV vaccine, 15 bats of each species bats were divided into three groups, the control group, the second group was given two doses of inactive RABV vaccine of 100µl and then sampled the blood on the tenth day, the third group was given three doses with the same concentration and blood sampled on the fourteenth day, after that, we performed the tests of blood parameters. The Results showed: No significant different in the weight and dimensions of spleen in both species during the experiment stages. The highest concentration of total protein was observed between the control group and the 10th day group in Rousettus aegyptiacus, while the less increase was between the 10th day group and 14th day group in in Rousettus aegyptiacus. Accordingly, it was concluded that there is a kind of relationship between the two species of bats Rousettus aegyptiacus & Myotis myotis according to the immune response of Rabies according to their immune response to the rabies vaccine. The two species of bats had the same response mechanism to the inactive rabies vaccine, with only differences in total protein concentrations.